Pengaruh Harga dan Fasilitas Terhadap Niat Berkunjung Kembali Ke Kawasan Luar Pura Uluwatu - Muliawati, Ni Kadek Diah; Susianti, Hartanti Woro; Sukariyanto, I Gede Made (Pusat Penelitian dan Pengabdian kepada Masyarakat Politeknik Pariwisata Bali, 2023)
In recent years, the number of tourists visiting the Outer Area of Uluwatu Temple has experienced growth fluctuations. These fluctuation factors can be identified through visitor complaints related to prices and services available in the area. This study aims to evaluate the impact of price and facilities on the desire to make a repeat visit to the Uluwatu Temple Outer Area. This study uses quantitative and qualitative data types. The research sample group consisted of 115 respondents consisting of tourists who had come to the area. The sampling method used is accidental sampling method. The collected information is processed using a quantitative method through validity testing, reliability testing, classical assumption testing, multiple linear regression, T testing, and F testing. The findings from this study indicate that individually, price has a significant and positive impact on the intention to return to visit , while facilities also have a positive and significant impact on the intention to return to visit. In addition, simultaneously, prices and facilities positively and significantly influence the desire to return to visit the Uluwatu Temple Outer Area